A study of performance and deterioration of lubricating oil of diesel generator by biodiesel blends - Sathapornprasath, Kitti; Charoenkul, Tawatchai (Asia-Pacific Journal of Science and Technology, 2017)
The purposes of this research were to study performance of diesel generator and to analysis of exhaust emission when a combination of biodiesel (Methyl Ester) and diesel fuel was used as tested fuel. A diesel generator used in this study was MERCEDES BENZ OM 421 rated at 159 kW. The various ratios of biodesel (B0, B5, B10, B15, B20, B25, B50, B75 and B100 by volume) were applied during experiment in order to evaluate the engine performance. The results showed that an increase in biodiesel ratio led to an increase in density and viscosity of the fuel. The injection efficiency of nozzle was thus decreased leading to an incomplete combustion. In addition, fuel consumption and specific fuel consumption increased when the ratio of biodiesel increased. In terms of exhaust emission analysis, it was found that when the ratio of biodiesel increased, the amount of CO, HC and black smoke were decreased. The amount of NOx increased, however. It was also found that when biodiesel B20 was used, the amount of wear metals in lubricating oil decreased. The nitrate reaction and the oxidation reaction were reduced as well.